Peritoneum‐Inspired Janus Porous Hydrogel with Anti‐Deformation, Anti‐Adhesion, and Pro‐Healing Characteristics for Abdominal Wall Defect Treatment. Issue 15 (3rd March 2022) - Liang, Weiwen; He, Wenyi; Huang, Rongkang; Tang, Youchen; Li, Shimei; Zheng, Bingna; Lin, Yayu; Lu, Yuheng; Wang, Hui; Wu, Dingcai
Abstract: Implantable meshes used in tension‐free repair operations facilitate treatment of internal soft‐tissue defects. However, clinical meshes fail to achieve anti‐deformation, anti‐adhesion, and pro‐healing properties simultaneously, leading to undesirable surgery outcomes. Herein, inspired by the peritoneum, a novel biocompatible Janus porous poly(vinyl alcohol) hydrogel (JPVA hydrogel) is developed to achieve efficient repair of internal soft‐tissue defects by a facile yet efficient strategy based on top‐down solvent exchange. The densely porous and smooth bottom‐surface of JPVA hydrogel minimizes adhesion of fibroblasts and does not trigger any visceral adhesion, and its loose extracellular‐matrix‐like porous and rough top‐surface can significantly improve fibroblast adhesion and tissue growth, leading to superior abdominal wall defect treatment to commercially available PP and PCO meshes. With unique anti‐swelling property (maximum swelling ratio: 6.4%), JPVA hydrogel has long‐lasting anti‐deformation performance and maintains high mechanical strength after immersion in phosphate‐buffered saline (PBS) for 14 days, enabling tolerance to the maximum abdominal pressure in an internal wet environment. By integrating visceral anti‐adhesion and defect pro‐healing with anti‐deformation, the JPVA hydrogel patch shows great prospects for efficient internal soft‐tissue defect repair. Abstract : A peritoneum‐inspired Janus porous poly(vinyl alchohol) (PVA) hydrogel patch with unique asymmetric cell‐adhesion behaviors and excellent anti‐swelling characteristics demonstrates anti‐adhesion, pro‐healing, and anti‐deformation properties simultaneously, leading to superior repair effect of abdominal wall defects.